General geographical maps on the territory of western Ukrainian lands during the period of 1919-1939: directions, peculiarities and results of mapping - Бондаренко, Е.; Іщук, А. (Київський національний університет імені Тараса Шевченка, 2013)
It was researched that the main directions of cartographic and geodetic services (offices) of Poland, Romania, Czechoslovakia and the USSR, whose activity in 1919-1939 was concentrated in War departments were: republication of the existing general geographical maps completed by different publishers and issued in different years, content updating of the existing maps according to the condition of an area and the period of it's creation, development of the new cartographical works with general geographical content based on surveying. A direct connection between the peculiarities and the directions of the general geographical mapping on the western territories in the interwar period is established. The results are represented by the original general geographical maps of a certain scale range, which covers western territories in accordance with the directions and mapping features. The practical use of the existing maps is possible, particularly in the medium of computer informational system, the creation of which is substantiated by methodological principles that define its functionality.

Досліджено, що основними напрямами роботи картографо-геодезичних служб Польщі, Румунії, Чехословаччини та СРСР, діяльність яких у 1919–1939 роках концентрувалась у військових відомствах, були: перевидання існуючих загальногеографічних карт різних видавців та років створення; оновлення змісту карт, існуючих відповідно до стану місцевості та періоду створення; розробка нових картографічних творів загальногеографічного змісту на основі проведення топографічної зйомки. Встановлено прямий зв'язок особливостей та напрямів загальногеографічного картографування західноукраїнських територій у міжвоєнний період. Результати представлені оригіналами загальногеографічних карт певного масштабного ряду, які покривають західноукраїнські території відповідно до напрямів та особливостей картографування. Практичне використання існуючих карт можливе, зокрема, у середовищі комп'ютерної інформаційної системи, створення якої обґрунтоване методологічними принципами, що визначають її функціональні можливості.
Загальногеографічні карти на західноукраїнські території періоду 1919-1939 років: напрями, особливості та результати картографування
Keywords: general geographical mapping; republication of general geographical maps; content updating of the existing maps; surveying; scale range; informational system; functionality; загальногеографічне картографування; перевидання загальногеографічних карт; оновлення змісту карт; топографічна зйомка; масштабний ряд; інформаційна система; функціональні можливості